PENINGKATAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN MODEL KOOPERATIF TIPE THINK PAIR SHARE (TPS) DI SD - Syahrir, Didi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Starting from the problem that: Often Teachers teach a lesson using the method of lecture, question and answer so that students are bored in learning. Teachers in the learning process that is active while students passively, Because students learn more individualistic eventually many students score below the KKM. Based on the research that has been Carried out using the Model Cooperative Study Think Pair Share, IPS student learning outcomes can be improved. Keywords: learning outcomes; teaching social studies; model of cooperative Type Think Pair Share